Pengaruh Structural Empowerment Pada Job Satisfaction Dengan Mediasi Role Stress Dan Organizational Support - Indrianingsih, Tiwik Budiarti Mastuti; Laksmi Riani, Asri (MDP Student Conference, 2024)
This study explores how role stress, specifically role ambiguity and role conflict, impacts the well-being of healthcare professionals, focusing on nurses. It aims to understand the influence of role stress on job satisfaction, the role of structural empowerment in enhancing job satisfaction, and the mediating effect of role stress on the connection between organizational support and job satisfaction. Utilizing a quantitative approach, including descriptive analysis and SEM-PLS techniques through the SmartPLS application, the study involved employees at Indriati Solo Baru Hospital in Sukoharjo. Findings reveal a detrimental effect of role stress on job satisfaction, with a positive contribution from structural empowerment. Mediation analysis demonstrates that structural empowerment mitigates role stress, while organizational support mediates the relationship between structural empowerment and job satisfaction. In conclusion, role stress adversely impacts job satisfaction, yet the positive influence of structural empowerment and organizational support helps alleviate this effect, offering valuable insights into factors influencing job satisfaction within the healthcare sector.